Antimicrobial activity of ethanolic leaf extract of chayote [Sechium edule (Jacq.) swartz] tops - Federico, Joan R. (College of Home Economics, University of the Philippines, 2009)
ABSTRACT The antimicrobial activity of ethanolic leaf extract of Sechium edule (Jacq.) Swartz was evaluated using disc diffusion assay, minimum inhibitory concentration (MIC) test, and minimum bactericidal concentration (MBC) test, against Escherichia coli (ATCC 25922) and Salmonella Typhimurium (UPCC 1768). A more pronounced antimicrobial activity was observed on S. Typhimurium than on E. coli. The crude extract showed zone inhibition sizes of 0.58 ± 0.69 mm and 0.06 ± 0.03 mm for S. Typhimurium and on E. coli, respectively. Extract concentrations of 2.5% and 12.5% were found to inhibit the growth of S. Typhimurium and E. coli, respectively. Concentrations of 50% and 75% were necessary to kill S. Typhimurium and E. coli, respectively. The total phenolic content of various extract concentrations ranged from 0.01 ± 0.01 to 0.79 ± 0.11 mg GAE per ml solvent. No significant correlation (P>0.05) was observed between total phenolic content and antimicrobial activity of the extract. The results obtained might be considered sufficient to warrant further studies focusing on the isolation of active component/s responsible for antimicrobial activity of S. edule extract, determination of specific mode of action and toxicity levels of these compounds, and utilization of the extract as antimicrobial agent in foods.